Implementation method of integrated ultrahigh-temperature environmental barrier composite coating

Through integrated coating preparation process, combined with high-entropy alloys, MO-SI-B multi-layer structures, alloy oxides and other technical means, the problem of defects of existing coating in high temperature and complex environments has been solved. Protective effect and longer service life.

CN119352016AActive Publication Date: 2025-01-24SHANGHAI JIAOTONG UNIV +1

Patent Information

Application Number
CN202411472619.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing high-temperature ablation coating is prone to defects such as cracks and peeling under the conditions of emergency cold and rapid thermal cycles, and cannot effectively cope with the effects of complex gas components such as high-temperature water vapor, resulting in a shortening of the coating life.

Method used

Adopt integrated coating preparation processes, first pre-applied high-entropy alloys or its boronized layers on the surface of the substrate, and then pre-coated pure molybdenum metal pre-coating. Form an orderly MO-SI-B multi-layer structure, and finally the cold-spray alloy oxide outside the composite self-healing layer to form a water-resistant steam layer.

Benefits of technology

It achieves effective protection for a variety of refractory alloys in a wide temperature range, improves the integrity of the coating, high-temperature oxidation resistance and durability in complex environments, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352016A_ABST
    Figure CN119352016A_ABST
Patent Text Reader

Abstract

The invention relates to a method for realizing an integrated ultrahigh-temperature environmental barrier composite coating, which comprises the following steps of: pre-coating a high-entropy alloy or a boride layer thereof and a molybdenum metal pre-coating on the surface of a substrate, and carrying out silicon-boron co-embedding deposition through a pre-oxidation process to form an ordered Mo-Si-B multi-layer structure in the molybdenum metal layer; a composite coating composed of metal silicide and silicon dioxide is cold-sprayed on the Mo-Si-B multilayer structure, and a composite self-healing layer of a three-dimensional network structure is formed through high-temperature thermal sintering; and alloy oxide is subjected to cold spraying or magnetron sputtering outside the composite self-healing layer to form the water vapor resistant layer. According to the invention, through an integrated coating preparation process, advantages of different components are complementary, and effective protection of various refractory alloys in a wide temperature range (room temperature-1700 DEG C) can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of new material coatings, specifically a method for realizing an integrated ultra-high temperature environment barrier composite coating. Background Art

[0002] The key factor for the new multi-principal refractory alloy (RMPEA or RHEA) to work stably and for a long time in an oxidizing environment is the formation of a protective oxide layer. However, in a high-temperature oxidizing environment, most refractory alloys are difficult to form a dense oxide layer or the formed oxide layer is often difficult to provide protection due to the high oxygen diffusion rate. During the thermal cycle process and thermal load, the severe cracks generated in the stress-promoted coating will lead to coating damage and failure. A protective coating compatible with the substrate can provide protection to the substrate without affecting the overall performance of the substrate. Under the conditions of rapid cooling and heating cycles, the difference in thermal expansion coefficients between the coating and the substrate of the existing high-temperature ablation-resistant coating makes the coating structure prone to defects such as cracks and peeling, and the coating cannot cope with the working environment with complex gas components. For example, the high-temperature water vapor H2O in the working gas will react with the SiO2 component in the coating, quickly consume SiO2, and reduce the life of the coating. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a method for realizing an integrated ultra-high temperature environment barrier composite coating. Through an integrated coating preparation process, the advantages of different components are complemented, thereby providing effective protection for a variety of refractory alloys in a wide temperature range.

[0004] The present invention is achieved through the following technical solutions:

[0005] The invention relates to a method for realizing an integrated ultra-high temperature environment barrier composite coating, comprising the following steps: pre-coating a high entropy alloy or a boride layer thereof on a substrate surface, and then pre-coating a pure molybdenum metal pre-coating layer, and performing vacuum high temperature sintering; performing silicon-boron co-embedding deposition, and forming an ordered Mo-Si-B multilayer structure in the molybdenum metal layer through a pre-oxidation process; cold-spraying a composite coating composed of metal silicide and silicon dioxide on the surface of the Mo-Si-B multilayer, and forming a composite self-healing layer with a three-dimensional network structure after high temperature air sintering; cold-spraying or magnetron sputtering an alloy oxide on the outside of the composite self-healing layer to form a water vapor resistant layer, and performing a sintering treatment.

[0006] The high entropy alloy or its boride refers to: W-Mo-Ta-Nb, W-Mo-Ta-Nb-Zr, W-Mo-Ta-Nb-Hf, W-Mo-Ta-Nb-V or its boride (W-Mo-Ta-Nb)B, (W-Mo-Ta-Nb-Zr)B, (W-Mo-Ta-Nb-Hf)B or (W-Mo-Ta-Nb-V)B.

[0007] The metal silicide and silicon dioxide mentioned above refer to: MoSi2, WSi2 and SiO2.

[0008] The alloy oxide is: HfO2, ZrO2, MgO or CrTaO4.

[0009] The present invention relates to an integrated ultra-high temperature environment barrier composite coating prepared by the above method, comprising: a reinforced diffusion barrier layer composed of a high entropy alloy or its boride, a Mo-Si-B anti-oxidation diffusion barrier layer, a composite self-healing layer and a water vapor resistant layer which are sequentially located on a substrate. Technical Effects

[0010] The present invention utilizes an integrated composite coating design method, and through a spraying process, a thermal sintering process, an embedding co-deposition process, and a pre-oxidation treatment, etc., adds a diffusion-resistant refractory high-entropy alloy or its boride, an adjustable three-dimensional network structure self-healing layer, and a high-temperature water vapor-resistant layer to the original Mo-Si-B coating. Compared with the prior art, the present invention realizes the integration of multiple functions of the coating, greatly improving the integrity, high-temperature oxidation resistance, and durability in complex environments of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a flow chart of the present invention;

[0012] Figure 2 This is a schematic diagram of the coating structure of the present invention;

[0013] Figure 3 The cross-sectional backscattered electron images of the Mo pre-coating and Mo-Si-B coating samples prepared by the two-step method in the embodiment after being exposed to air at 1300° C. for 10 hours and the schematic diagram of the element distribution of silicon and molybdenum are shown;

[0014] Figure 4 (a) is a mass change curve of the uncoated and coated samples during the isothermal oxidation test at 1300°C in the embodiment; (b) is a schematic diagram of a cross-sectional backscattered electron image of the coated sample after 50 hours of isothermal test;

[0015] Figure 5 (a) is a weight change curve during the thermal cycle test in the embodiment, and the inset shows the coating sample after 750 hours of cycling; (b) is a backscattered electron cross-sectional image of the coating sample after 100 cycles; (c)-(d) are schematic diagrams of backscattered electron cross-sectional images of the coating sample after 750 cycles;

[0016] Figure 6 This is a physical picture of the integrated composite coating on the TZM disc;

[0017] Figure 7The graph is the relationship between the weight change and exposure time of the integrated composite coating sample in an oxidizing environment at 1600°C for 100 hours;

[0018] Figure 8 This is a cross-sectional view of the composite coating after undergoing a 1600°C, 4×25 hour thermal cycle in the embodiment;

[0019] Fig. 9 The cross-sectional view of the composite coating after the Mo-Si-B coating (B layer) is subjected to air oxidation pretreatment at 1300° C. for 75 hours, and then the complete coating is subjected to thermal cycling at 1600° C. for 4×25 hours;

[0020] Fig.10 Schematic diagram of the thermal expansion coefficient adjustment mechanism of the self-healing composite layer. DETAILED DESCRIPTION

[0021] This embodiment relates to a method for implementing a diffusion barrier layer, a Mo pre-coating layer and a Si-B embedding co-deposition, a self-healing layer and a water vapor resistant layer on a high entropy alloy substrate, and verifies that the coating system can be applied to a conventional refractory alloy system, including:

[0022] Step 1, preparing a W-Mo-Ta-Nb-V multi-principal refractory alloy substrate (RMPEA) with an equiatomic ratio by arc melting;

[0023] Preferably, the ingot is turned over five times in this embodiment to achieve homogenization.

[0024] According to the arc melting, after annealing at 1800° C. for 50 hours, the dendritic structure in the original cast sample was completely removed, and the composition was fully homogenized.

[0025] Step 2: applying the Mo-Si-B coating to the RMPEA refractory alloy substrate as a substrate in two steps, specifically comprising:

[0026] 2.1. After preparing the refractory high entropy alloy diffusion barrier layer and Mo pre-coating layer by spraying slurry on the substrate, the slurry was dried in air and heated to less than 1×10 -5 The temperature is slowly raised and lowered in a high vacuum of mBar (rate <200℃ / h), and sintered at 1300-1800℃ for 2-10 hours.

[0027] The slurry is obtained by mixing 99.9% purity, 1-5 micron metal powder and 2.0% by weight of 1000-4000 mPa·s hydroxypropyl cellulose as a binder in ethanol, and specifically comprises:

[0028] i. preparing a refractory high entropy alloy or its boride slurry, mixing the refractory high entropy alloy powder and cellulose in a certain proportion, dissolving them in alcohol and mixing them thoroughly to form a uniform slurry;

[0029] ii. Prepare Mo slurry: dissolve Mo powder and cellulose powder in alcohol in a certain proportion and mix them thoroughly to form a uniform slurry.

[0030] Preferably, in this embodiment, before spraying, the substrate is ground to remove sharp edges and then sandblasted to increase surface roughness.

[0031] The spraying uses a compressed air spray gun to evenly spray the refractory high entropy alloy / boride and Mo metal slurry onto the surface of the substrate.

[0032] The sintering is preferably carried out at a heating / cooling rate of 15°C / min to reach 1750°C and sintering for 2 hours.

[0033] 2.2. Si-B package atmosphere infiltration process: After Si, B and activator powders were mixed and ground for 30 minutes to obtain a uniform mixture, Al2O3 filler was added, and then the Mo pre-coated sample was embedded in a sealed alumina crucible and then loaded into a sealed alumina tube filled with argon in the furnace for deposition treatment.

[0034] The mass ratio of Si powder to B powder is 35:1.

[0035] Preferably, Al2O3 is used as an inert filler and NaF is used as an active agent.

[0036] The deposition process is carried out at a temperature of 1000° C. for 50-100 hours, preferably at 1000° C. with an argon gas flow of about 15 ml / min for 50 hours.

[0037] 2.3. Exposure in air at 1300°C for 10-30 hours to generate a protective multilayer structure.

[0038] The powder coating includes: 34.03% by weight of Si (99.5% purity, 44 microns), 0.97% by weight of B (99% purity, 44 microns), 2.5% by weight of NaF activator (99.99% purity) and 62.5% by weight of Al2O3 filler (99.7% purity, 180 microns).

[0039] The samples obtained in multiple steps 2 were subjected to constant temperature oxidation analysis and thermal cycle oxidation analysis, that is, the coating samples were taken out, rinsed with pure water, and after removing the surface adhesion powder, they were placed in alcohol or acetone for ultrasonic cleaning for 10 minutes. After obtaining a clean and smooth coating sample, ① a spherical coating sample with a diameter of 2.5 mm was placed in a crucible and kept in a protective argon atmosphere during heating and cooling. When the sample reached 1300°C, 20 volume % O2 and 80 volume % Ar oxidation atmosphere were introduced to obtain a constant temperature oxidation analysis sample, or ② an irregular rectangular coating sample with a size of about 6×2×2 mm was placed in a tube furnace with both ends partially open to the outdoor air for thermal cycle testing, and the hot zone temperature in the furnace was 1300°C. For each cycle, the sample was placed on an alumina plate, placed in the furnace for 60 minutes, and then taken out and cooled in air for 10 minutes to room temperature (23°C) to obtain a rapid cooling and rapid heating cycle test sample.

[0040] Preferably, the flow rate of the constant temperature oxidizing gas in this embodiment is 100 mL / min.

[0041] like Figure 4 The elemental analysis results show that there are clear boundaries between the Mo-Si-B / Mo pre-coating and the Mo pre-coating / MPEA substrate, indicating that the mutual diffusion between the Mo pre-coating and the MPEA substrate is very slow during the sintering and gas infiltration process.

[0042] like Figure 3 As shown, a cross-sectional BSE (backscattered scanning electron) image of the coating after the initial oxidation test in air at 1300°C. The multilayer structure formed in the coating is the result of phase sequencing developed along the multi-component diffusion path. From the outermost layer to the innermost layer, they are aluminum borosilicate, MoSi2, Mo5Si3 (T1), Mo5SiB2 (T2) and Mo pre-coating. Some small holes were introduced in the first spraying step of the Mo pre-coating, and most of them were filled with Al2O3 in the polishing agent during the embedding co-deposition infiltration and polishing process. However, considering that the difference in the coefficient of thermal expansion (CTE) in the multilayer structure will introduce stress, these small holes do not have an adverse effect on the coating. In fact, these small holes can accommodate the stress in the coating and help to suppress cracking during thermal cycling. Similarly, the distribution of test elements proves that there is a clear boundary between the coating and the substrate.

[0043] Isothermal and thermal cycling tests were performed on uncoated and two-step coated RMPEA samples at 1300°C. The mass change curves of the samples are shown in Figure 2. Figure 4 a. The uncoated bare RMPEA sample experienced a rapid weight gain in the first two hours, followed by a rapid weight loss for the remainder of the time. In contrast, the two-step coating provided strong protection to the substrate with only a weight change of -3.4 mg / cm 2. Figure 5 The mass change curve and cross-sectional morphology of the thermal cycle samples were obtained. The coating samples were subjected to 750 cycles of 1300°C thermal cycle testing, and the mass change was only -1.4 mg / cm 2 .

[0044] The 1300℃ isothermal oxidation experiment proved that the coating has parabolic oxidation kinetics. The coating sample was subjected to a thermal cycle test from 1300℃ to room temperature. After 750 hours of testing (each cycle stayed in the hot zone for 1 hour), the integrity of the sample was maintained and the mass change was only 1.4mg / cm 2 . The durability of the coating is attributed to its self-healing ability. The coating is able to accommodate internal stresses caused by thermal shock, and any cracks that form will be filled by borosilicate glass to prevent further oxidation damage. The initially formed Mo-based T2 layer acts as a first diffusion barrier, preventing elements from diffusing into the substrate, maintaining the integrity and functionality of the coating. After long-term use, due to the capture of boron, a solid solution T2 layer as well as a (RMPEA)-B layer are formed at the RMPEA substrate interface, acting as a second diffusion barrier and boron reservoir for the coating system. These diffusion-resistant layers significantly improve the integrity and working life of the coating.

[0045] Step 3: preparing a composite self-healing coating and a water vapor resistant layer, specifically comprising:

[0046] 3.1. Prepare refractory alloy silicide and SiO2 powder slurry, mix the two powders and cellulose in alcohol according to proportion, stir and mix thoroughly to form a uniform slurry;

[0047] 3.2. Use a compressed air spray gun to evenly spray the slurry onto the sample surface;

[0048] 3.3. Prepare refractory alloy oxide powder slurry, mix the oxide powder and cellulose evenly in proportion and dissolve them in alcohol to form slurry;

[0049] 3.4. Spray the refractory alloy oxide slurry evenly onto the sample surface;

[0050] 3.5. The sample is placed in air, heated to 1500-1600℃ and sintered for 2 hours to form a composite self-healing coating and a water vapor resistant layer. Figure 6 As shown, it is the morphology of the coating sample; Figure 7-Figure 9 Shown are the oxidation test results of the integrated composite coating.

[0051] Preferably, the thermal compatibility control method of the three-dimensional mesh self-healing layer is as follows: Fig.10As shown, by controlling the volume fraction of metal silicide in the composite coating (such as the volume fraction of MoSi2), the overall thermal expansion coefficient CTE of the composite coating can be calculated. By adjusting the proportion of silicide such as MoSi2 to make the thermal expansion coefficients of the composite coating and the substrate similar, the thermal stress caused by the difference in thermal expansion coefficients during service can be reduced, and the thermal mechanical compatibility of the composite coating and the substrate can be achieved.

[0052] Compared with the prior art, the present method can achieve matching of the thermal expansion coefficient with the substrate material by adopting a composite self-healing layer with an adjustable thermal expansion coefficient, thereby enhancing the thermomechanical compatibility of the coating system with the substrate, reducing or avoiding cracks in the coating during service, and improving the durability and service life of the coating; by integrating the outermost water vapor resistant layer composed of refractory alloy oxides, the interior of the coating can be protected from contact with complex environmental atmospheres such as water vapor, which can effectively slow down the consumption of coating components and improve the coating integrity and service life.

[0053] The above-mentioned specific implementation can be partially adjusted in different ways by those skilled in the art without departing from the principle and purpose of the present invention. The protection scope of the present invention shall be based on the claims and shall not be limited by the above-mentioned specific implementation. Each implementation scheme within its scope shall be subject to the constraints of the present invention.

Claims

1. A method for realizing an integrated ultra-high temperature environment barrier composite coating, characterized in that: After pre-coating a high entropy alloy or its boride layer and a molybdenum metal pre-coating layer on the substrate surface, silicon-boron co-embedded deposition is performed through a pre-oxidation process to form an ordered Mo-Si-B multilayer structure in the molybdenum metal layer; a composite coating composed of metal silicide and silicon dioxide is cold-sprayed on the Mo-Si-B multilayer structure, and a composite self-healing layer with a three-dimensional network structure is formed through high-temperature thermal sintering; alloy oxides are cold-sprayed or magnetron-sputtered outside the composite self-healing layer to form a water vapor resistant layer.

2. The method for realizing the integrated ultra-high temperature environment barrier composite coating according to claim 1 is characterized in that: The high entropy alloy or its boride refers to: W-Mo-Ta-Nb, W-Mo-Ta-Nb-Zr, W-Mo-Ta-Nb-Hf, W-Mo-Ta-Nb-V or its boride (W-Mo-Ta-Nb)B, (W-Mo-Ta-Nb-Zr)B, (W-Mo-Ta-Nb-Hf)B or (W-Mo-Ta-Nb-V)B.

3. The method for realizing the integrated ultra-high temperature environment barrier composite coating according to claim 1 is characterized in that: The metal silicide and silicon dioxide are: MoSi2, WSi2 or SiO2.

4. The method for realizing the integrated ultra-high temperature environment barrier composite coating according to claim 1 is characterized in that: The alloy oxide is: HfO2, ZrO2, MgO or CrTaO4.

5. The method for realizing the integrated ultra-high temperature environment barrier composite coating according to claim 1 is characterized in that: The Mo-Si-B multilayer structure is prepared by the following method: 1) After preparing a Mo pre-coating layer by spraying the slurry on the substrate, the pre-coating layer was dried in air and slowly heated and cooled in a high vacuum and sintered; 2) After Si, B and activator powders were mixed and ground, Al2O3 filler was added, and the Mo pre-coated sample was embedded in a sealed alumina crucible, and then loaded into a sealed alumina tube in a furnace for deposition treatment; 3) Exposure to high temperature air generates a protective multi-layer structure.

6. The method for realizing the integrated ultra-high temperature environment barrier composite coating according to claim 5 is characterized in that: The slurry is obtained by mixing 99.9% purity, 1-5 micron Mo powder and 2.0% by weight of 1000-4000mPa·s hydroxypropyl cellulose as a binder in ethanol, specifically comprising: a) preparing a refractory high entropy alloy or its boride slurry, mixing the refractory high entropy alloy powder and cellulose in a certain proportion, dissolving them in alcohol and fully mixing them to form a uniform slurry; b) preparing a Mo slurry, dissolving the Mo powder and cellulose powder in alcohol in a certain proportion, and fully mixing them to form a uniform slurry.

7. The method for realizing the integrated ultra-high temperature environment barrier composite coating according to claim 5 is characterized in that: The sintering is carried out at a heating / cooling rate of 15°C / min to reach 1750°C and sintering for 2 hours.

8. The method for realizing the integrated ultra-high temperature environment barrier composite coating according to claim 5 is characterized in that: The mass ratio of Si powder to B powder is 35:

1.

9. The method for realizing the integrated ultra-high temperature environment barrier composite coating according to claim 1, characterized in that: The composite self-healing coating and water vapor resistant layer are prepared by the following methods: a) preparing refractory alloy silicide and SiO2 powder slurry, mixing the two powders with cellulose in alcohol in proportion, and fully stirring to form a uniform slurry; b) using a compressed air spray gun to evenly spray the slurry onto the sample surface; c) preparing refractory alloy oxide powder slurry, mixing the oxide powder and cellulose in proportion and dissolving them in alcohol to form a slurry; d) evenly spraying the refractory alloy oxide slurry onto the sample surface; e) placing the sample in air, heating it to 1500-1600°C and sintering it for 2 hours to form a composite self-healing coating and a water vapor resistant layer.

10. An integrated ultra-high temperature environment barrier composite coating prepared according to the method of any one of claims 1 to 9, characterized in that: include: A reinforced diffusion barrier layer, a Mo-Si-B diffusion barrier layer, a composite self-healing layer and a water vapor resistant layer are sequentially arranged on the substrate.

Citation Information

Patent Citations

  • Niobic alloy high temperature antioxidation silicide coating and preparation method thereof

    CN101200801A

  • Preparation method of thermal barrier coating containing long-service-life antioxidant bonding layer

    CN104630686A

  • Boride modified glass ceramic based composite high-temperature oxidation resisting coating and preparation method thereof

    CN106587629A

  • Composite protective coating integrating oxidation resistance and interface diffusion resistance and preparation method thereof

    CN112962012A

  • Environmental barrier coating with excellent CMAS corrosion resistance, and preparation method thereof

    CN113860920A

Cited By

  • Implementation method for improving high-temperature chemical stability and mechanical compatibility of transition metal silicon boride coating

    CN120505588A